2006
DOI: 10.1080/00015458.2006.11679862
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Rectal Cancer Patients in Belgium 1997–98 and the Potential Benefit of a National Project

Abstract: Significant improvement seems to be achievable. Implementation of the PROCARE guidelines with quality assurance through prospective registration in a specific database, however, is a crucial prerequisite for credible audit of performance and feedback to individual teams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…A few years, later the local recurrence rate was reduced to 8% [15] and from 1994 to 1998 the overall survival rate increased significantly [16], thereby proving a significant improvement with optimized surgery alone. There are few national rectal cancer studies outside Scandinavia: A Belgian study showed a relative 5‐year survival rate of 59% from 1997 to 1998 [17]. In Austria the relative 5‐year survival increased from 44% in 1998 to 64% in 2002 in men, and in women from 46% to 67%; the authors considered the improvement to be caused partly by modern imaging and new oncological treatment [18].…”
Section: Discussionmentioning
confidence: 99%
“…A few years, later the local recurrence rate was reduced to 8% [15] and from 1994 to 1998 the overall survival rate increased significantly [16], thereby proving a significant improvement with optimized surgery alone. There are few national rectal cancer studies outside Scandinavia: A Belgian study showed a relative 5‐year survival rate of 59% from 1997 to 1998 [17]. In Austria the relative 5‐year survival increased from 44% in 1998 to 64% in 2002 in men, and in women from 46% to 67%; the authors considered the improvement to be caused partly by modern imaging and new oncological treatment [18].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study on rectal cancer treatment in Belgium over 1997 and 1998 showed a high variability in outcome with 5-year relative survival varying between provinces, from 48 to 71% [32]. Stimulated by the marked improvement of outcome in rectal cancer treatment in nationwide audit registrations elsewhere in Europe, Belgian surgeons initiated the Project on Cancer of the Rectum (PROCARE).…”
Section: Belgiummentioning
confidence: 99%
“…This is consistent with the experience in both North America and Europe. [9][10][11][12] Although tumor and pathological factors, such as stage Radiotherapy utilization in rectal cancer and site, should be the primary determinant of radiotherapy utilization, it is evident that other factors are just as significant. It has been found that sociodemographic factors such as patient ethnicity 22 and socioeconomic status 10 are influential, particularly in North America.…”
Section: Discussionmentioning
confidence: 98%
“…3,4 Guidelines have been introduced for the management of rectal cancer internationally 5,6 and in Australia 7,8 but despite this radiotherapy utilization remains low. 2,[9][10][11][12] The Australian National Colorectal Cancer Survey indicates that only 36% of stage II and 55% of stage III rectal cancers received radiotherapy. 2 Based on studies of the optimal utilization of radiotherapy for rectal cancer, it is estimated that up to 60-70% of rectal cancer patients stand to benefit from radiotherapy.…”
Section: Introductionmentioning
confidence: 99%